Sistemas de classificações geomecânicas: Classificações geomecânicas aplicadas aos domínios estruturais na rampa de exploração e túnel de drenagem na mina de Chuquicamata – Chile - DIAS, Rogério Aguirre (2019)
This monograph presents the results obtained in the characterization of structural domains and the geomechanical classification of rock mass intercepted by means of an exploration ramp and drainage tunnel. This work was carried out in the Chuquicamata mine which is found along the Coldeco Norte Company in Chile. Geological discontinuities (faults, fractures and joints) were studied with the aid of Dip’s 5.108 Rocscience software. This software was used in the drawing up of Schmidt-Lambert stereographic networks for every individual geological structural domain. Subsequently, the distribution pattern of the discontinued structures that were mapped was determined. Based on the structural data, it was possible to define eight (8) structural domains, each having different characteristics. Additionally, an examination of the rock mass - intercepted by underground excavations - was also carried out for the purpose of geomechanical classification. The Barton, N. (1974) system of geomechanical classification was used. In order to define the geomechanical conditions as well as the quality of the rock mass which was intercepted along the subterranean excavations, Barton’s Q-system was correlated to Bieniawski’s geomechanical classification system (RMR, 1989). The values obtained regarding the geomechanical classification of these different systems are presented in 2D and 3D. These representations provide better spatial visualization of the quality of the mass excavated during the implementation of these structures, which were used for estimating the support necessary for stabilization. The purpose of establishing these classifications was to create a parallel between the methodological parameters applied and the results obtained. It was possible to observe a considerable dependency of the geomechanical partition on the geological model. These results, represented by mean of layouts and the 3D model of RMR and Qsystem values, proved to be useful in locating zones of weakness (lower quality) in the rock mass. This largely favored the extraction planning executed by the Chuquicamata Underground Project, a mining operation scheduled to start in 2018. During this operation, the block caving method will be used to allow for bulk mining.